Tomorrow there will be apricots : a novel - Soffer, Jessica (Houghton Mifflin Harcourt, 2013)
Lorca spends her life poring over cookbooks, making croissants and chocolat chaud, seeking out rare ingredients, all to earn the love of her distracted chef of a mother, who is now packing her off to boarding school. In one last effort to prove herself indispensable, Lorca resolves to track down the recipe for her mother's ideal meal, an obscure Middle Eastern dish called masgouf. Victoria, grappling with her husband's death, has been dreaming of the daughter they gave up forty years ago. An Iraqi Jewish immigrant who used to run a restaurant, she starts teaching cooking lessons; Lorca signs up. Together, they cook, but they also begin to suspect they are connected by more than their love of food. Soon, though, they must reckon with the past, the future, and the truth--whatever it might be.